PERLINDUNGAN HAK ANAK DALAM KELUARGA SEBAGAI IMPLIKASI ISBAT NIKAH - Fardlillah, Qonita; Candrawati, Siti Dalilah (LPPM STAI Muhammadiyah Probolinggo, 2025)
Unregistered marriages cannot be recognized as valid by the state and will experience obstacles when dealing with marriage documents as evidence of marriage so that they will not get a marriage certificate and have an impact on the rights of the wife and children that should be received in the marriage. If the marriage is not registered in order to be registered in order to fulfill the rights of children in the family, a legal procedure is required through an application for marriage confirmation to the Religious Court. Marriage confirmation is carried out in order to obtain legal certainty so that the marital status can be registered at the Religious Affairs Office as well as an effort to protect the legal rights of children born from their marriage. This literature study aims to determine the importance of marriage confirmation for unregistered marriages with all their reasons in order to guarantee legal certainty, especially the fulfillment of children's rights that are material and non-material. The findings of this literature study show that the application for marriage confirmation granted by the Religious Court provides legal certainty for married couples and children. In the context of married couples, ownership of a marriage certificate can then be used to take care of personal documents such as family cards, child birth certificates and related documents. In the context of children's rights, unregistered marriages that are confirmed will potentially provide protection for children's rights including children's identity rights, children's rights to become heirs, rights to welfare and child protection.